2017
DOI: 10.20944/preprints201709.0132.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conceal Carry and Race: A Test of Minority Threat Theory in Law Generation

Abstract: Conceal carry weapon (CCW) laws have generated a great deal of public discussion in the past decades, but little social science attention. Scholarly worked on the topic has been focused on finding potential effects of such laws on crime and victimization; little has attempted to explain the trends behind the adoption of the laws. This paper attempts to fill that gap by testing a series of hypotheses grounded in minority threat approaches. Our paper examines whether or not changes in the racial and ethnic compo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…For example, schools located in states that showed more support for Donald Trump’s 2016 Presidential campaign are significantly more likely to have student shooting sports organizations. This finding aligns with previous studies that have shown that support for the Republican Party is central to understanding gun‐related outcomes (Mullins and Kavish 2017; Steidley 2018; Stucky et al 2008). Yet, the presence of a permissive handgun law in a state appears to play no role in the presence of student shooting sports organizations.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…For example, schools located in states that showed more support for Donald Trump’s 2016 Presidential campaign are significantly more likely to have student shooting sports organizations. This finding aligns with previous studies that have shown that support for the Republican Party is central to understanding gun‐related outcomes (Mullins and Kavish 2017; Steidley 2018; Stucky et al 2008). Yet, the presence of a permissive handgun law in a state appears to play no role in the presence of student shooting sports organizations.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, to assess the role of state laws regarding gun rights, we constructed a dichotomous variable to indicate whether a state generally grants its residents the right to carry a concealed handgun (yes=“1”). Restrictive states were defined as having implemented limited, “may issue” laws, while permissive states were defined as having implemented “shall issue,” “constitutional carry,” or reasonable issue statutes (Mullins and Kavish 2017; NRA‐ILA 2019a; Steidley 2018). Data from the NRA‐ILA (2019a) were used to construct this variable.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Combined with the fact that whites historically have viewed themselves as being responsible for keeping minorities from legally obtaining and carrying weapons (Light ), it is plausible that many white voters may choose to maintain more restrictive gun laws in some instances . Indeed, the possibility of such a threat‐induced outcome is not entirely unprecedented, as a recent cross‐sectional study by Mullins and Kavish () finds some evidence—in the form of a negative relationship between changes in black population size and the proportion of county‐level votes for less restrictive state CCW laws in Missouri—consistent with this line of reasoning. Accordingly, this study hypothesizes that in states with larger black and Hispanic populations, more permissive CCW laws will be less likely (H5 and H6).…”
Section: Past Research Theory and Hypothesesmentioning
confidence: 90%